Assessing the Impacts of Climate Change on Agriculture and Livelihoods in the Potohar Plateau, Pakistan - Muhammad Waqas; Dr Aneela Afzal, (Dialogue Social Science Review (DSSR), 2025)
This paper is an exploratory study on how climate change has been perceived to affect agricultural livelihoods at the Potohar plateau, one of the places that is most vulnerable to the degradation of the environment. A structured questionnaire given to 400 respondents is used in this research to examine the impact of dynamic climatic conditions, including rising temperatures, irregular rainfall patterns, the prevalence of pests, and extreme weather conditions, on crop production, livestock health, and traditional farming technology. The other question that the study looks into is how well local communities are implementing adaptive methods and how they are ready to engage themselves as participants of climate-smart agricultural training programs. The results indicate that most of the respondents confirm the fact that there are serious climate related shocks to agricultural productivity and income. The majority of farmers state that the traditional activities are getting less and less productive, and they also see the alterations in botany of the crops as well as the growing stress of the animals. Correlation analysis reveals positive relationship between perceived impact and adoptive measures of the adaptive, which means the stronger the impact is perceived to be, the greater the chances are to find measures towards the solutions. On the other hand, constraints that have a moderate association with challenges associated with adoption of adaptation strategies entail the following: shortage of resources, shortage of knowledge, as well as institutional constraints. Positively, a high number of the respondents show readiness to take part in training programs and people habits to be innovative. In addition, local knowledge has been playing a crucial role in the context of local adaptation efforts. The paper has reached the conclusion that both the indigenous wisdom and modern climate-resilient methods should be combined, enhancing institutional support, and extending outreach under some capacity-building activities targeted at agricultural resilience building. The study can be of use to better comprehend the grass root climate vulnerabilities and provide practical guidelines to policymakers, extension workers or development practitioner who may be interested in improving the adaptive and sustainable livelihoods of the people in the climate vulnerable areas such as Potohar. Keywords: Climate Change, Agriculture livelihood, livestock health, Climate-resilient, Potohar